FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN SUSTAINABILITY REPORT ASSURANCE DI INDONESIA - Amelia Kristina Lumban Toruan; Aditya Septiani (Diponegoro Journal of Accounting, 2020)
This study aims to provide evidence that corporate governance as well as pressure from stakeholders is a factor in the demand for insurance sustainability reports for companies listed on the Indonesia Stock Exchange who are participants and winners of the Sustainability Reporting Award in 2016-2018. The independent variables used in this study are owner concentration, institutional ownership, CSR committee, pressure from stakeholders, industries that are close to customers, industries that are sensitive to the environment, and membership in industries with high pressure from employees. The dependent variable used in this study is the sustainability report assurance.This study uses a logistic regression analysis method with secondary data obtained using a sample collection method that is purposive sampling. The research sample consisted of 24 companies with criteria of companies listed on the Stock Exchange that published sustainability reports and were registered as participants and winners of the SRA in 2016, 2017 and 2018. The research data are secondary data from the financial statements and annual reports of non-financial companies in 2016-2018.The results of this study indicate that only the presence of CSR and industri committees with high proximity to consumers is positively and significantly correlated to the probability of demand for sustainability assurance.